PENGEMBANGAN MODEL PEMBELAJARAN KARAKTER BERBASIS SAINTIFIK DI SEKOLAH DASAR - Marlina, Ina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2015)
The purpose of this article is to develop the learning model based on scientific approach in the elementary school. The stages of scientific approach are in these models. Based on the nature of character itself, the character learning models can be divided into two kinds, namely reflective model and rational construction model. The development of education in elementary school has been orientating not only in cognitive aspect but also the value aspect that presents the character education in elementary school. The development of character education have to appropriate with the identity of that character education. Having the comprehension of character learning model, the teachers will reach the purpose as well as to solve the problems especially in education nowadays.